AI-ASSISTED ACADEMIC WRITING: OPPORTUNITIES, LIMITATIONS, AND BEST PRACTICES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Artificial Intelligence (AI) has significantly transformed academic writing by improving productivity, language quality, and research efficiency. AI-powered tools are now wide and discusses the best practices for using AI responsibly in education and research. The study highlights that AI can save time and enhance writing quality; howly used by students, researchers, and educators for generating ideas, editing texts, correcting grammar, summarizing articles, and organizing academic content. This article examines the major opportunities and limitations of AI-assisted academic writingever, it also raises concerns regarding academic integrity, plagiarism, misinformation, and overreliance on technology. The article concludes that AI should be used as a supportive tool rather than a replacement for human critical thinking and creativity.